Max's Chocolate Chicken - Wells, Rosemary (New York : Dial Books for Young Readers, 1989)
Max and his sister Ruby go on an egg hunt and vie with each other for the prize--a chocolate chicken.
Keywords: Rabbits -- Fiction; Brothers and sisters -- Fiction; Easter -- Fiction